Musculoskeletal Disorders in Dentistry: An Insight into Dental Techniques and Practices - Kashif, Mehwash; Ashar, Aman; Rehman, Amna; Aleem, Abdul; Hashmi, Sidra-tul-Muntaha; Ali, Muhammad Yousuf (UI Scholars Hub, 2025)
Objective: Musculoskeletal disorders (MSDs) are common workplace hazards in dentistry resulting from poor ergonomics and static postures, which lead to back, neck, and upper limb (shoulder, elbow, wrist, and hand) problems among dentists, resulting in harm to their health, productivity, and career. This study aimed to assess the frequency of MSDs, risk factors related to MSDs, and awareness of ergonomics among clinicians. Methods: Data were collected from 400 dental professionals, including house officers, postgraduate trainees, general dentists, and teachers/consultants, each with at least 12 months of practice. Data were collected using a structured, closed-ended questionnaire. Before data collection, ethical approval was obtained from the Institutional Review Board of the Karachi Medical and Dental College (ESRC/KMDC/069/2023). Results: It was found that only 12.8% of respondents (n = 49, all postgraduate trainees) regularly adjusted their chairs to an ergonomic position. Maintaining posture for > 40 min (p = 0.025), uncomfortable stools (p = 0.034), repeated motions for more than two hours (p = 0.003), maintained non-neutral postures for > 2 h (p = 0.002), and repetitive wrist flexion or extension (p = 0.014) were all significant risk factors. Conclusion: There is a need to incorporate ergonomics and posturedontics into undergraduate and continuing education curricula to minimize the risk of developing MSDs and to support sustainable careers.